Types of Slang Analysis Found in “Kevin Hart” Twitter Account - Putu Erika Permata; I Gede Agoes Caskara Surya Putra (BULLET : Jurnal Multidisiplin Ilmu, 2023)
Many people use social media as a medium to interact with others, especially on Twitter. We usually see teenagers use slang words to communicate on social media Twitter and we know it as internet slang. This research aimed to discover the types of slang on the “Kevin Hart” Twitter account. In this study, the descriptive qualitative method was used to explain what types of slang and the meaning of slang. The writer used a theory of the types of slang by Allan and Burridge (2006). After collecting the data, the writer tabulated the slang words that had been found; divided the types and characteristics of the words; interpreted the meanings; and drew a conclusion. This study finds the types of slang in each variation, there are fresh and creative 3 data, flippant 3 data, imitative 13 data, acronym 1 data, and clipping 2 data.